Rehabilitation Programs in Fulfilling Inmates’ Financial Obligations: A Prison Officers’ Perspective - Az-Zahra, Salma Fathimah (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
This study examines the fulfillment of financial obligations by inmates and the various challenges encountered in implementing rehabilitation programs within correctional institutions. Employing a mixed-methods approach, the research integrates quantitative data—collected through questionnaires distributed to prison officers—and qualitative insights derived from in-depth interviews and content analysis of social media platforms. A case study of a particular inmate, such as Zul Zivilia, is presented to provide a concrete illustration of financial support practices during incarceration. The findings reveal that rehabilitation programs have made a significant contribution to skill development, enhanced self-confidence, and support for inmates in meeting their financial responsibilities toward their families. Nevertheless, the effectiveness of these programs continues to face several constraints, including limited funding, a lack of collaboration with external stakeholders, and pervasive social stigma, especially on digital platforms such as TikTok. The case of Zul Zivilia demonstrates the efforts of an inmate to fulfill financial obligations through productive activities within prison, despite facing negative public perceptions in the digital sphere. Accordingly, this study recommends strengthening cross-sectoral partnerships, enhancing rehabilitation facilities, and promoting legal and social literacy as critical measures to ensure the long-term success of inmate rehabilitation and social reintegration programs. [Penelitian Penelitian ini mengkaji pemenuhan nafkah oleh narapidana serta berbagai tantangan yang dihadapi dalam pelaksanaan program pembinaan di lembaga pemasyarakatan. Metode yang digunakan adalah mixed methods, yakni menggabungkan pendekatan kuantitatif melalui penyebaran kuesioner kepada petugas lembaga pemasyarakatan dan pendekatan kualitatif melalui wawancara mendalam serta analisis konten media sosial. Studi kasus terhadap narapidana, seperti Zul Zivilia, diangkat sebagai ilustrasi konkret atas praktik pemenuhan nafkah selama masa pidana. Hasil penelitian menunjukkan bahwa program pembinaan di lembaga pemasyarakatan telah memberikan kontribusi signifikan dalam pengembangan keterampilan, peningkatan kepercayaan diri, serta dukungan terhadap pemenuhan tanggung jawab nafkah keluarga oleh narapidana. Namun demikian, efektivitas program masih menghadapi sejumlah kendala, antara lain keterbatasan anggaran, minimnya kolaborasi dengan pihak eksternal, serta kuatnya stigma sosial yang berkembang di ruang digital, khususnya di platform seperti TikTok. Studi kasus Zul Zivilia menggambarkan upaya narapidana dalam menjalankan kewajiban nafkah melalui aktivitas produktif di dalam lapas, meskipun harus berhadapan dengan prasangka negatif dari masyarakat digital. Oleh karena itu, penelitian ini merekomendasikan penguatan sinergi lintas sektor, peningkatan sarana pembinaan, serta edukasi literasi hukum dan sosial guna mendukung keberhasilan program pembinaan dan proses reintegrasi sosial narapidana secara berkelanjutan.]